Interplanetary Diaspora and Fourth World Representation in Celu Amberstone's "Refugees". Issue 1 (April 2017) - Sanchez-Taylor, Joy
Abstract : This work examines Celu Amberstone's "Refugees" as an example of a science fiction text that creates a postcolonial consciousness through its embodiment of Fourth World theory. I argue that by bringing together the experiences of Indigenous and diasporic groups, Amberstone represents a postcolonial view of space colonization that focuses on the consequences of displacement and the experience of colonized peoples. Amberstone depicts a multitude of complex relations between the Benefactors, the originally settled human population of Tallav'Wahir, and the new human refugees to address issues of colonization while highlighting the resilience of diasporic and Indigenous peoples.